The relationship between living environment, well‐being and lifestyle behaviours in young women in Shiraz, Iran. (24th November 2015) - Salehi, Asiyeh; Harris, Neil; Sebar, Bernadette; Coyne, Elisabeth
Abstract: There has been increasing interest in understanding the influence of the living environment on individual and population health. While our understanding of the connection is growing, there has been limited published research focusing on socially and economically transitioning countries such as Iran or specific populations such as young women. This study explores the relationship between the physical and social living environment with well‐being outcomes and lifestyle behaviours of young women in Shiraz, Iran, in 2013. Using a cluster convenience sampling technique, 391 young Iranian women with the mean age of 27.3 (SD: 4.8) participated in a cross‐sectional survey (response rate 93%). A scale adapted from the British General Household Social Capital scale was used to assess living environment characteristics. The International Health and Behaviour survey, Satisfaction with Life Scale (SwL) and WHO Quality of Life questionnaire (WHOQOL‐BREF) were used to measure lifestyle behaviours and well‐being. The findings showed a moderate level of satisfaction with participants' living environment, with a mean score of 38.5 (SD: 7.7; score range: 11–45). There were correlations between physical and social neighbourhood environment, lifestyle behaviours and well‐being outcomes ( P < 0.05). Multiple regression analysis showed that the characteristics of living environments were determinants of quality of life (QoL), including physical, psychological, social and environmental QoL, as well as SwL ( P < 0.05). Perceptions of individuals about their living environment issues were associated with demographic variables including ethnicity, income, level of education and occupation status. The current study shows how characteristics of the physical and social living environments play a significant role in shaping well‐being and lifestyle behaviours among young Iranian women. Hence, there is a need for more focused attention to the meaning, measurement and building of neighbourhood livability, including both physical and social aspects of neighbourhood, in order to support QoL and SwL among young Iranian women, and enhance their healthy lifestyle behaviours.